Reintroduction of stimulant treatment for patients with ADHD, after stimulant-related psychosis. (May 2014) - Chammas, Marc; A Ahronheim, Gerald; Hechtman, Lily
ADHD is a common condition that affects a large proportion of the child, adolescent and adult population. One of the most widely used medications for treating this illness are psychostimulants, which are generally well tolerated. Nevertheless, one of the rare side effects includes the development of psychotic symptoms. Generally, these symptoms are cleared when the medication is discontinued. There have been several case reports in the literature pertaining to these side effects. Most of them solely involve discontinuation of the medication, but there are four case reports where rechallenging with stimulant medication occurred, with only two of these resulting in recurrence of psychotic symptoms. We report three additional cases where rechallenging with stimulant medication did not result in reappearance of psychotic symptoms. Possible risk factors for developing such side effects and hypothesized mechanisms are discussed.